Kinematic analysis on sliding shot put - Li, P.; Zhou, J. (International Journal of Experimental and Computational Biomechanics, 2018)
In this paper, a comprehensive three-dimensional kinematic quantitative analysis has been applied to analyse the movement and biomechanics of throwing technology of a Chinese excellent women's shot. The filming is conducted with a multi-camera 3D imaging system during the championship. A star high titanium 3D signal TEC V1.0C three-dimensional video analysis software system is used for parsing with the RBI web parsing resolution. The human body model applied is Japan Matsui (16, 22 key parameters). The throwing movement is divided into five main stages: the oscillating acceleration phase, the sliding stage, the transition phase and the last stage of throwing. Research analysis for each phase has focused on different biomechanical characteristics and parameters. The key parameters for the throwing movement of the subject in this work is critically compared to other data of related parameters of the domestic and foreign excellent athletes with reference to the general rule of shot put techniques. The key issues associated with the throwing and future biomechanical training is discussed.